Solution-plasma-induced oxygen vacancy enhances MoOx/Pt electrocatalytic counter electrode for bifacial dye-sensitized solar cells - Li, Yanan; Wang, Yinglin; Lin, Jianfei; Shi, Yuming; Zhu, Kuangyu; Xing, Yanmei; Li, Xiaofei; Jia, Yuwen; Zhang, Xintong (Frontiers in Energy Research, 2022)
Bifacial dye-sensitized solar cells (DSCs), harvesting light from both front and rear sides, are potential high-efficiency photovoltaic devices with broad application environments. The electrocatalytic counter electrodes (CEs) of bifacial DSCs could determine the light-harvesting from the rear side and the charge collection of solar cells through electrocatalytic processes. As a result, high-activity and high-transparency CEs are essential for bifacial DSCs. Recently, novel CEs based on strong metal-support interaction (SMSI) have been proven to improve the catalysis and stability of the metal catalytic sites and induce great efficiency increase of bifacial DSCs. However, the contradiction between the transparency and conductivity of support is still a major challenge for the application of SMSI-based CEs on bifacial DSCs. Herein, we utilized a solution plasma (SP) method to introduce oxygen vacancies into a transparent MoOx support film. These SP-induced oxygen vacancies improved the conductivity of MoOx and the interaction between the metal Pt catalytic sites and support, thereby enhancing the catalytic activity and transparency of MoOx/Pt CEs. Consequently, the bifacial DSCs with MoOx/Pt CEs yielded a high efficiency of 7.56% and 6.41% with the front- and rear-side illumination, respectively. This impressive front-to-rear efficiency ratio of 85% indicates that the SP method has a positive effect in constructing high-performance CEs and other electrocatalytic materials based on the SMSI.